Noninvasive and Quantitative Monitoring of the Distributions and Kinetics of MicroRNA-Targeting Molecules in Vivo by Positron Emission Tomography - Jussi Mäkilä; Anu Kiviniemi; Tiina Saanijoki; Heidi Liljenbäck; Meeri Käkelä; Satish Jadhav; Päivi Poijärvi-Virta; Harri Lönnberg; Tiina Laitala-Leinonen; Pasi Virta; Anne Roivainen (AMER CHEMICAL SOC, 2022)
MicroRNAs (miRNAs) are endogenous, small, noncoding ribonucleic acids (RNAs) that bind to the 3' untranslated regions of messenger RNAs (mRNAs) and induce translational repression or mRNA degradation. Although numerous studies have reported that miRNAs are of potential use for disease diagnostics and gene therapy, little is known about their fates in vivo. This study elucidated the whole-body distributions and kinetics of intravenously administered miRNA-targeting molecules in vivo by positron emission tomography (PET) imaging. A 22-mer sequence targeting miR-1513 was conjugated with three different chelators and labeled with gallium-68 (Ga-68). These tracers were compared with a scrambled 22-mer sequence; 22-mer with two single base substitutions; anti-miR-34 22-mer; hexathymidylate (T-6), a 6-mer sequence; and an unconjugated chelator. miR-15b was chosen as a target because it is important for bone remodeling. All three Ga-68-labeled anti-miR-15b molecules had similar biodistributions and kinetics, and they all accumulated in the bones, kidneys, and liver. The bone accumulation of these tracers was the highest in the epiphyses of long tubular bones, maxilla, and mandible. By contrast, the scrambled 22-mer sequence, the 6-mer, and the unconjugated chelator did not accumulate in bones. PET imaging successfully elucidated the distributions and kinetics of Ga-68-labeled chelated miRNA-targeting molecules in vivo. This approach is potentially useful to evaluate new miRNA-based drugs.